YOUTH, CREATIVITY, COPYRIGHT, AND CULTURAL NUANCE IN THE DIGITAL AGE - Sherly Haristya (The Indonesian Journal of Communication Studies, 2015)
This research is trying to see how some digital natives in Indonesia deal with copyright in the digital age since internet enable everyone to become a consumer, distributor, and also producer of content at the same time. With different characteristics of digital natives in Indonesia, the current work thus seeks to fill the gap for Indonesia’s context that has not been touched by the previous research from Palfrey, Gasser, Simun, and Barnes (2009). With the use of qualitative method, the research conducted to a group of young people age from 14-19 years old that come from social class A and B. They were asked to fill closed and open-ended questionnaire and continued with an in dept interview for those who showed interest in creation process on the internet. It was found that there is a great distance between copyright concepts to digital natives in this research. Besides, there were also misconceptions in understanding copyright law. Moreover, it was found lack of participations in creating cultural works on the internet from these digital natives. They had not been armed with technical and social knowledge to participate in creating and influencing cultural production and development.